Taxonomic value of morphological and morphometrical characters in the immature stages of four species of Kampimodromus Nesbitt (Acari: Phytoseiidae) from Italy and Croatia - Cargnus, Elena; Zandigiacomo, Pietro (Zootaxa, 2014)
The immature stages of four species of Kampimodromus Nesbitt (Acari: Phytoseiidae) from Italy and Croatia have been studied and identified both at stage and species level. Larval stages of Kampimodromus corylosus Kolodochka and all immature stages of Kampimodromus ericinus Ragusa di Chiara & Tsolakis and Kampimodromus langei Wainstein & Arutunjan are described for the first time. The relative length of the posterior dorsal setae Z4 make the larvae of Kampimodromus aberrans (Oudemans) easy to separate from those of the other three species. Nymphs of each species had similar diagnostics to the adults of the respective species. Ontogeny of the idiosomal and leg setation of the Kampimodromus immatures studied in comparison to the available data from immatures of other phytoseiid species is discussed. The length of seta Z4 in the K. aberrans larva, and the number of setae on leg IV of the deutonymphs of the four Kampimodromus species, are proposed as additional taxonomic traits for Phytoseiidae.